EFFECT OF USING TEACHING MEDIA TOWARDS STUDENT'S SPEAKING SKILLS - Sayyid Khairunas; Udin Jaenudin; Rizky Mirani Desi Pratama (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The research aims to determine how teaching media and vocabulary mastery affects students'speaking skills at SMAN Kabupaten Cirebon. The population of this research was all students atSMA Negeri in Kabupaten Cirebon, speaking skills as part of English. The sample of thisresearch is taken based on the multiple-stage method with similar characteristics andprobability. In this research, the writer randomly takes the ten great students at SMA Negeri inKabupaten Cirebon into the sample; one experiment group and one control group. In thisresearch, there are two kinds of instruments: one is to measure the student's speaking skill, andthe other is to determine the student's learning styles. Data analysis used SPSS version 20, with asignificant level of = 0.05. The requirement analysis uses a normality test, homogeneity test, andtwo-way ANOVA. There is a significant interaction effect of teaching media and vocabularymastery on students' speaking skills. The value of Fo = 5.225 proves that, and Sig = 0.025<0.05. There is a significant effect of teaching media on students' speaking skills. That is provedby Fo = 13.822 and sig = 0.000 < 0.05. There is a significant effect of vocabulary mastery onstudents' speaking skills. That is proved by Fo = 36.140 and Sig. 0.000 > 0.05.